Distribusi pendapatan dalam pembangunan - Suharto Suharto (Economic Journal of Emerging Markets, 2001)
The lameness problem of income distribution has become a debatable issue among economic soon after the emerge of new awareness about this problem in the developing countries in 1970th. A development strategy, which is oriented in the growth in fact, has caused some serious problems in the income distribution, as well as the damage of environment.